2016
DOI: 10.3892/ijo.2016.3778
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin1 overexpression in hypopharyngeal squamous cell carcinoma: A new promoter in FaDu cell proliferation and migration

Abstract: Stathmin1, a microtubule-destabilizing phosphoprotein, is considered to play a crucial role in regulating cellular microtubule dynamics and controlling mitosis. Previous studies have showed that STMN1 is highly expressed in many human malignancies and is related to development, invasion and metastasis of tumors. However, its expression pattern, clinical performance and functional roles in hypopharyngeal squamous cell carcinoma (HSCC) have not been addressed. In this study, we found that STMN1 was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Our results also support this idea; we found cell cycle arrest in the G1/S phase following the knockdown of STMN1 expression. The same results were also reported in hypopharyngeal squamous cell carcinoma by Chen et al (32).…”
Section: Discussionsupporting
confidence: 87%
“…Our results also support this idea; we found cell cycle arrest in the G1/S phase following the knockdown of STMN1 expression. The same results were also reported in hypopharyngeal squamous cell carcinoma by Chen et al (32).…”
Section: Discussionsupporting
confidence: 87%
“…STMN1 is a phosphoprotein that functions to destabilize microtubules by facilitating microtubule depolymerization. STMN1 has been reported to be upregulated across many kinds of cancers, and its high expression correlates with a poor prognosis 34,35 . Previous studies have indicated that STMN1 inhibits EMT and the metastatic behaviours of epithelial cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…STMN1 is also a biomarker in certain types of neoplasm. It serves important functions in cell cycle progression, mitosis, signal transduction and cell migration ( 35 37 ). There is no study reporting directly on the effect of STMN1 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%